Criminalization of Adultery under New Criminal Code: Morality and the Protection of Citizens’ Private Rights - Taun Taun; Fareed Mohd Hassan (Universitas Muhammadiyah Purwokerto, 2026)
The enactment of Criminal Code Number 1 of 2023 has sparked new controversy in society, particularly regarding the criminalization of adultery, regulated in Articles 411 and 412. These articles stipulate that adultery is a complaint-based offense that can only be prosecuted if a complaint is filed by the husband, wife, or parents of unmarried parties. This policy has drawn criticism for its perceived intrusion into citizens' private sphere, although the government argues that the regulation is intended to protect the family institution and public morality. This article aims to examine the criminalization of adultery from the perspective of balancing the protection of morality with respect for private rights in a democratic state governed by the rule of law. The approach used is normative juridical, with analysis of legislation, legal literature, and comparative studies. The results of the study indicate that the criminalization of adultery must be treated with caution to prevent it from becoming a tool to legitimize state intervention in the private sphere, while still upholding the principles of proportionality and human rights.